НЕЛІНІЙНІСТЬ АНАЛОГО-ЦИФРОВОГО ПЕРЕТВОРЮВАЧА НА БАЗІ СИГМА-ДЕЛЬТА МОДУЛЯТОРА ДРУГОГО ПОРЯДКУ - Цзюнь , Су; Кочан , Р.В.; Кочан , О.В. (Інститут електродинаміки НАН України, Київ, 2014)
There is developed the simulation model of analog to digital converter, which is based on single-bit second order sigma-delta modulator. Implementation of this model provides investigation the influence of components parameters on integral nonlinearity of analog to digital converter. There are identified character of the curve of integral nonlinearity and integrators’ nonlinearity decreasing coefficients by analog to digital converter. References 10, figure 1.